Canada's Arctic Council chairmanship (2013-2015): a post-mortem - Exner-Pirot, Heather (Canadian foreign policy journal, 2016)
On 15 May 2013, Canada assumed the two-year chairmanship of the Arctic Council, an intergovernmental forum established in 1996 that addresses common issues faced by Arctic states and indigenous peoples in the areas of environmental protection and sustainable development. The Canadian chairmanship disappointed many. By Arctic Council standards, it was controversial, in particular as regarded its focus on development, its hard line with Russia, and its difficult style of management under Minister for the Arctic Council Leona Aglukkaq. Based on its activity and outcomes, however, the Canadian chairmanship can be described as a success. Its achievements include the establishment of an Arctic Economic Council; the conclusion of framework action plans on reducing black carbon and methane emissions and preventing marine oil pollution; and many other projects, reports and institutional improvements led by the six Working Groups, three Task Forces and Permanent Secretariat. In outlining the 2013-2015 Canadian Arctic Council's defining events and outcomes, and documenting the perceptions held by relevant observers and stakeholders, this article concludes that while the Canadian agenda had merit, and the Arctic Council itself achieved a number of important outcomes, the Canadian chairmanship provoked deserved criticism and undermined Canada's reputation in the region.